2004
DOI: 10.1177/1329878x0411300110
|View full text |Cite
|
Sign up to set email alerts
|

Resisting Peripheral Exports: Al Jazeera's War Images on us Television

Abstract: This paper describes work that is underway to develop a framework for the analysis of media flows from periphery to centre — the phenomenon known in globalisation studies as ‘contra-flow’. The framework proposed in this paper challenges the fundamentals of current studies of peripheral exports, which arguably fail to consider Western resistance involved in the representation of peripheral networks due to the presumption that ‘contra-flow’ single-handedly supports the cultural heterogenisation paradigm. The pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Al-Jazeera’s exclusive images and reports were imported by leading western stations, triggering objections that the practice imposed a non-western perspective of the hostilities on western stations (Jasperson and El-Kikhia, 2002, 2003; Volkmer, 2002). However, a comprehensive study that tracked the resonance of Al-Jazeera Arabic news items in the US media strongly contradicted this notion and found that Al-Jazeera Arabic’s materials were actually persistently manipulated by US stations to fit within the western perspective (Azran, 2004; Galily et al , 2016; Samuel-Azran et al , 2016). Online, Al-Jazeera’s materials were re-presented primarily on liberal platforms and were rejected by conservative platforms (Samuel-Azran, 2006).…”
Section: Sport Following: Ethnocentric or Truly Global?mentioning
confidence: 99%
“…Al-Jazeera’s exclusive images and reports were imported by leading western stations, triggering objections that the practice imposed a non-western perspective of the hostilities on western stations (Jasperson and El-Kikhia, 2002, 2003; Volkmer, 2002). However, a comprehensive study that tracked the resonance of Al-Jazeera Arabic news items in the US media strongly contradicted this notion and found that Al-Jazeera Arabic’s materials were actually persistently manipulated by US stations to fit within the western perspective (Azran, 2004; Galily et al , 2016; Samuel-Azran et al , 2016). Online, Al-Jazeera’s materials were re-presented primarily on liberal platforms and were rejected by conservative platforms (Samuel-Azran, 2006).…”
Section: Sport Following: Ethnocentric or Truly Global?mentioning
confidence: 99%
“…The analysis of the platform used aims to understand the extent that the hashtag was used on the more elitist platform Twitter (Paul et al, 2019) versus the more popular Facebook and Instagram. Finally, the analysis of the political inclination aims to illuminate whether the users behind the protests are mostly conservatives, as past studies showed the Republicans in the United States specifically were behind the banning of Al-Jazeera America (Azran, 2004;Samuel-Azran & Hayat, 2017) as well as other Al-Jazeera outlets, a comparable Qatari ambition to gain global recognition, on grounds of religious/racial motivations. Or, alternatively, comprised mostly by liberals, indicating that the motivation was more likely human rights.…”
Section: Qatar 2022 World Cup and The State's Delusionsmentioning
confidence: 99%
“…However, studies show that some bodies, most notably led by U.S. Republicans, persistently tried to block Al-Jazeera's ability to broadcast to U.S. audiences and thus gain credibility as a legitimate news source. First, a large-scale study of the representation of Al-Jazeera Arabic identified that the main U.S. news networks, but most notably the Fox News Channel, persistently censor and manipulate images from Al-Jazeera (Azran, 2004). Next, another study documented how Republican bodies were able to block Al-Jazeera English from findings a US satellite or cable provider host to carry the channel as Republican organizations and members threatened to discontinue their subscriptions due to an alleged anti-American bias of Al-Jazeera (Samuel- Azran, 2010).…”
Section: Qatar's Global Ambition and Subsequent Resistance To Its Act...mentioning
confidence: 99%
“…Recent 'peripheral visions' (Sinclair et al, 2002) qualify the overarching claims of Western media dominance. Included here are studies of new regional media formations and regional media production (Chalaby, 2002;Cunningham et al, 1998;Sinclair et al, 2002;Sreberny-Mohammadi, 1991), contra-flows from new regional players (Azran, 2004;El-Nawawy and Iskandar, 2003), discerned 'mini-cultural imperialisms' enacted between former colonies (Sonwalkar, 2001), and the national 'domestication' of news exchange materials and the reporting of global events (Clausen, 2003;Cohen et al, 1996). Together these open up a host of new dynamics and complexities in the study of global communication formations and flows.…”
Section: International and Global News Studies: The Democratic Lacuna In The Fieldmentioning
confidence: 99%